Bilingual Education Program: Teachers’ and Students’ Perspectives and Challenges - Mirizon, Soni; fauziah, Nurul; Silvhiany, Sary (Jurnal Pendidikan Progresif, 2020)
Bilingual Education Program: Teachers’ and Students’ Perspectives and Challenges. Objectives: The objectives of this study were to investigate the teachers’ and students’ perspectives of bilingual education program and the challenges faced. Methods: In this qualitative case study, the participants were the science teachers and the tenth-graders of the program. The data were gathered using interviews and observations and were analyzed by organizing and planning the results, paying attention to data, coding the data, generating the description and themes, and reflecting descriptions and themes. Findings: First, all science teachers and most students had positive perspectives and admitted the benefits of the program. Second, all the teachers and students faced challenges during the implementation of the program. Conclusion: All teachers and most students positively perceived bilingual education program. However, their positivity could not free them from facing challenges. Therefore, some improvements are required to enhance the program. Keywords: bilingual education, teachers, students, perspectives, challenges DOI: http://dx.doi.org/10.23960/jpp.v10.i1.202014